DISPUTE ANALYSIS OF CLAIMS FOR PATIENTS WITH COVID-19: A CASE STUDY AT HOSPITAL X CLASS B IN BANTUL REGENCY - Putri, Beby Antika; Hafidz, Firdaus; Hendrartini, Yulita (UI Scholars Hub, 2023)
The Indonesian Government established referral hospitals for COVID-19 as an effort in combating the pandemic. Referral hospitals for COVID-19 submit their services’ claims to the Ministry of Health. Hospital X in Bantul experienced challenges in submitting COVID-19 claims and underwent claim disputes which caused delays in payment process. This research aimed to explore the factors that led to the disputes over the COVID-19 claims. This descriptive research was conducted with a qualitative approach, using in-depth interviews and observations. The additional descriptive analysis used secondary data COVID-19 claim dispute file reports from 2020. The results showed that the highest criteria of disputed claims at Hospital X were the criteria for non- compliant guaranteed participants, incomplete claim files, non-compliant comorbid diagnoses, and identities that did not comply with the provisions. The causes of the disputes over claims for patients with COVID-19 included inaccurate history taking, differences in regulation perceptions between the provider and payer, PCR results were not provided, and doctors had a lack of understanding regarding the technical guidelines for COVID-19 claims. In addition, there were technical problems faced by the hospital during the process of submitting claims, including regulations were changed frequently, errors in applications, incomplete medical resumes, and unreadable doctors’ writings. Disputed claims did not affect the hospital cash flow, yet delayed the payment process to health workers, which might harm the quality of services.